1987
DOI: 10.1161/01.cir.76.2.312
|View full text |Cite
|
Sign up to set email alerts
|

Autologous blood perfusion for myocardial protection during coronary angioplasty: a feasibility study.

Abstract: lactate dehydrogenase, and potassium remained constant before and after the perfusion and the control inflations. The maximum pain score was significantly lower with the perfusion inflation (4.1 ± 0.8 vs 6.0 ± 0.9, p<.003). Relative to baseline, the maximum ST segment elevation during the perfusion inflation (0.5 ± 0.3 mm) was nearly one-fourth that during the control inflation (1.9 ± 0.6 mm, p<.02). Thus, myocardial protection with oxygenated autologous blood perfusion at rates of 60 ml/min appears to be a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 33 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…The results of the present study in swine are in line with a recent pilot study employing intracoronary preoxygenated HBOC-201 in five patients undergoing elective PCI in our center (20) and with earlier work demonstrating myocardial protection with oxygenated autologous blood perfusion at rates of 60 ml/min in a comparable model (16). Our results may be of importance to clinical practice since preoxygenated HBOC-201 can match the oxygen delivery role of endogenous blood on an equivalent-volume basis.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study in swine are in line with a recent pilot study employing intracoronary preoxygenated HBOC-201 in five patients undergoing elective PCI in our center (20) and with earlier work demonstrating myocardial protection with oxygenated autologous blood perfusion at rates of 60 ml/min in a comparable model (16). Our results may be of importance to clinical practice since preoxygenated HBOC-201 can match the oxygen delivery role of endogenous blood on an equivalent-volume basis.…”
Section: Discussionsupporting
confidence: 90%
“…Due to the high pressures required, there is slippage of the roller pumps, resulting in inadequate perfusion (8). Angiographic power injectors have to be filled with heparinized blood before perfusion can be realized (9). They have a volume of 500 ml; therefore, the time that perfusion can be maintained is limited (8.3 min at a flow rate of 60 mumin).…”
Section: Discussionmentioning
confidence: 99%
“…Lehmann and co-workers found that, in their system, hemolysis was negligible below 60 ml/min flow, but above 60 ml/min there was a sharp increase in hemolysis [52]. We evaluated the extent of mechanical hemolysis during active perfusion with the Corflo@ system [53].…”
Section: Mechanical Hemolysis During Active Hemoperfusionmentioning
confidence: 99%